Editorial: volatile organic compound analysis to improve faecal immunochemical testing in the detection of colorectal cancer—Authors' reply. Issue 4 (31st July 2021) - Chandrapalan, Subashini; Bosch, Sofie; Tyagi, Heena; Daulton, Emma; Cubiella, Joaquín; Guardiola, Jordi; Kimani, Peter; Mulder, Chris; Covington, James; Persaud, Krishna; de Meij, Tim G. J.; Altomare, Donato F.; et al.
LINKED CONTENT: This article is linked to Chandrapalan et al and Hanna & Cross papers. To view these articles, visit https://doi.org/10.1111/apt.16405 and https://doi.org/10.1111/apt.16471